Studies on the effect of gonadotrophin releasing hormone administration on conception rate following artificial insemination in cattle maintained under sub-temperate climate - SHARMA, AMIT; SINGH, MADHUMEET; VASISHTA, N K (The Indian Journal of Animal Reproduction, 2023)
In all, 346 animals comprising of 167 Jersey and 179 Jersey X Red Sindhi crossbred cows were inseminated artificially at livestock farm of Himachal Pradesh Krishi Vishvavidyalya, Palampur. Buserelin acetate and Gonadorelin were injected through intra muscular route for the treatment as GnRH analogues. Depending upon the groups, either single or double inseminations were performed in these cows. In double insemination group, the cows were reinseminated 24 hours after the first AI. Among the Jersey cows 59.6 and 53.8% animals conceived, following GnRH administration and 40.0 and 45.0% conceived in control group (without GnRH) following single or double insemination, respectively. Similarly, among crossbred cows, 58.and 55.5% animals conceived when inseminated along with GnRH and 45 .0 and 60.0% conceived in control groups following single and double insemination, respectively.